KKM-PKM and the Digital Age: Connecting Technology with the People of Padi Hamlet, Wajok Hilir Village - Rahmadhani, Daranti; Mayasari, Endah; Onenesti, Nola Angelika; Aulia, Faiza; Nurkhalish, Adil Imam; Muttaqin, Ahmad Rofiqul (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This research aims to explore the KKM-PKM program (Kuliah Kerja Mahasiswa-Pengabdian Kepada Masyarakat) nature of connecting technology with the community in Dusun Padi, Wajok Hilir Village. The background of this research is driven by the rapid development of digital technology that has not been fully utilized by the village community, through a participatory approach, this research identifies community needs and potential technologies that can be applied. The research method used is a qualitative approach with data collection techniques through interviews, observations, focus group discussions (FGDs) with local residents, and literature studies from previous research. The results showed that there was a gap in knowledge of digital technology among the people of Padi Hamlet. However, through the KKM program, students successfully introduced relevant digital applications and tools, such as the use of social media for marketing local products and digital skills training. The conclusion of this study confirms that the KKM program not only contributes to the improvement of technological knowledge in the community, but also strengthens social and economic connectedness. Recommendations for further development include the need for continuous training and support from local government to facilitate technology adoption in rural communities.